Group Guidance with Folklore Method as Alternative Developing Tolerance Character - Sri Hartini; Agus Supriyanto; Amien Wahyudi; Anwar Sutoyo; Rezki Perdani Sawai; Agungbudiprabowo Agungbudiprabowo (Universitas Ahmad Dahlan, 2020)
Diversity in Indonesia raises the tolerance problem. The research goal to find guidance and counseling services right to develop character tolerance. Research and development approach used in research. Research and development steps include preliminary study, development hypothetical group guidance model-based folklore, validation of expert judgment and expert practitioners, experimental test form group guidance model-based folklore on a limited basis — descriptive qualitative and descriptive quantitative in research analysis. The findings show Aspects of peace and mutual respect for students in the low category, during the self-awareness of students in the high category. School counselor role in group guidance services for prevention, development, understanding, and distribution of tolerance character. Tolerance characters appear in cognitive, affective, and psychomotor dimensions with indicators of peace, respect for differences and individuals, and awareness. Group guidance model-based folklore methods is the right solution for the internalization of character tolerance trough limited test with indicate that there was a significant change in tolerance level after the experimental analysis.